MOBILITAS SOSIAL MASYARAKAT DI DESA PALAS KECAMATAN PANGKALAN KURAS KABUPATEN PELALAWAN (Studi Kasus: Program 1.000 Tapak Rumah Gratis Tahun 2016) - Fitria, Almillah; Bahri, Syamsul (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This research was conducted in Palas Village, Pangkalan Kuras Sub-district, Pelalawan Regency. The purpose of this study was to find out how the social mobility of the society in Palas village with the program of 1,000 free home footprints and what are the factors that caused social mobility in Palas village. This study was conducted wtih Purposive sampling technique by setting as much 14 people as the the number of research subjects and 3 people as Key Informants. The author used qualitative descriptive method and data collection techniques by observation, interview and documentation. Based on the research, the author found that the program of 1.000 free home footprints was a program by providing free home footprints from the Head of Palas Village to the poor people in there. With the program there was social mobility in the society in Palas village by giving 1,000 free home footprints programs was: horizontal social mobility caused by migration and job movement. Vertical social mobility was the change of income level due to job shifting, home ownership, land ownership, ownership of household assets, ownership of motor vehicles and livestock. The existence of social mobility in Palas village caused by of the pushing factors and pulling factors of social mobility. The pulling factors was the existence of a 1,000 free home footprints programs, the desire of the society is to be able to get that programs. Besides of pulling factors, there was also the pushing factors of the desire to find a better job, the desire to earn a better income and also the narrowness of employment for people who come from outside the Palas Village. Keywords: Social Mobility, Society, 1000 Free Home Footprints Program